La Diabolisation dans La Guisiade (1589) de Pierre Matthieu et Le Guysien (1592) de Simon Bélyard - Jean-Claude Ternaux (Etudes Epistémè)
Devilish characterization in La Guisiade and Le Guysien can be accounted for by the political commitment of both playwrights as well as the deictic dimension of humanist tragedy. Through their questioning of values, they blacken the character of Henri III, often through slander. The king is blameworthy because he is a tyrant, whose cruelty likens him to the fiercest of animals. Besides, his reign is governed by hypocrisy, and he takes sides with the Huguenots. But the king is also presented as a truly devilish character. The tragedy then resembles the times’ libels and woodcuts. The king’s black minister, the duke of Épernon, urges him to fight against the Catholic League. Even worse, Henri III, as a true disciple of Machiavelli’s, claims he is God.